The persistence and clearance rate of human papilloma virus genotypes in urban Turkish women after one year [Bir yıl sonunda şehirde yaşayan türk kadınındaki human papilloma virus persistans ve klereansı] - (:unkn) unknown (Marmara University, 2012)
Objective: To evaluate the persistence of the different human papillomavirus (HPV) genotypes in women detected positive for HPV at Marmara University Hospital gynecologic outpatient clinics. Patients and Methods: Forty out of 79 women who had been tested positive for HPV DNA in our initial prevalance study were re-assessed after one year. HPV types were identified by polymerase chain reaction (PCR) and hybridization using a microarray. Results: One year after the initial assessment, 52.5% of the women had their initial HPV infection resolved and 35% of the women had acquired another HPV infection. The HPV DNA persistence was detected in 17.5% of the 40 women. Nine women had acquisition of HPV genotype by the same phylogenetic clade. 43.33% of high risk (HR) HPV type and 80% of the low risk (LR) HPV type infection had resolved. Conclusions: The persistence rate was increased in women with HR HPV types. Multiple and mixed HPV infections have an important impact on the persistence of HPV genotype. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Cervical cytology; HPV clearance; HPV genotype; HPV persistence